Design of emulsion-based adjuvants for animal vaccines - Burakova, Yulia (Kansas State University, 2018)
Vaccination is one of the most essential steps in controlling and preventing economically important infectious diseases in livestock. Vaccines need to be effective at producing a high level of immune responses that protect the animal from future encounters with infectious agents. Additional requirements for veterinary vaccines include safety, inexpensive components, and feasibility for large-scale production. These factors make emulsions attractive vaccine adjuvants. The use of emulsions as adjuvants (substances that help to amplify the immune responses to the antigen) has been explored for decades. However, emulsions are commonly produced with expensive and energy-demanding devices which impact the price of the adjuvant, therefore, affecting the price of the vaccines. This study examined low-energy emulsification methods to meet the requirements for a simple and low-cost vaccine manufacture that avoided utilizing complicated equipment. Spontaneous emulsification (SE) and phase inversion composition (PIC) was explored to formulate stable emulsions with nanometer droplet sizes. The study on the impact of oil composition on the formation of emulsions produced by SE revealed that addition of medium-chain triglycerides into the oil phase is beneficial for droplet size reduction and stability of emulsions. Box-Behnken design (BBD) was used to develop mathematical relationships between formulation variables and droplet size, polydispersity, zeta potential, and stability of emulsions formulated via SE. The BBD allowed the study of a simultaneous effect of multiple variables and formulate emulsions with certain physical characteristics, an effect that suggested that there was a more effective approach in designing complex systems like emulsions. New adjuvants containing mixtures of oils and surfactants were developed to produce emulsions with nanoscale droplet diameters and multiple water-in-oil-in-water structures via the PIC approach. The strong antibody responses and the absence of injection site side effects were observed in animals that received emulsion vaccines with experimental adjuvants. Additionally, inexpensive food-grade saponin extract was examined for stabilizing and increasing immunostimulatory activity of oil-in-water emulsion-based adjuvants. The adjuvants demonstrated high immune responses in pigs after co-administration with a subunit protein antigen.
Keywords: Emulsions; Vaccine adjuvants; Veterinary vaccines